3(2+x)=7+x

Simple and best practice solution for 3(2+x)=7+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2+x)=7+x equation:


Simplifying
3(2 + x) = 7 + x
(2 * 3 + x * 3) = 7 + x
(6 + 3x) = 7 + x

Solving
6 + 3x = 7 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
6 + 3x + -1x = 7 + x + -1x

Combine like terms: 3x + -1x = 2x
6 + 2x = 7 + x + -1x

Combine like terms: x + -1x = 0
6 + 2x = 7 + 0
6 + 2x = 7

Add '-6' to each side of the equation.
6 + -6 + 2x = 7 + -6

Combine like terms: 6 + -6 = 0
0 + 2x = 7 + -6
2x = 7 + -6

Combine like terms: 7 + -6 = 1
2x = 1

Divide each side by '2'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| p-10=-8 | | 3/5x5=7 | | (5y+7)-(3+4y)=12 | | 6.05=2.25+0.2(m-1) | | P+12=10 | | 6=2.25+0.2(m-1) | | 0=2cosx+2cos(2x) | | x-.1x=24251.76 | | x-.1x=2451.76 | | -P+20=13 | | 49u^2-9v^2=0 | | 9y+7x-3y-2y+17= | | Y=16x^2+64x | | .33x+12=2x-3 | | Y=2x+1forxandy | | 3(-1)+3(3/2)=9 | | x^2-7x+38=0 | | 1+t^2=0 | | 5(x+5)(x-10)= | | 37-4x=11 | | x-.15x=24251.76 | | 2(4x+1)=6x+10 | | 3+35x=20x+9 | | a-(-3a)=20 | | X^2=-4kx-1 | | 5y-3x-7+7x+13= | | 10-n=8 | | x+x+x+3=180 | | (x+3)(x+2)=(x+3)(5x+1) | | 3/5x6 | | 3/35x6 | | 55A^2+28A-3= |

Equations solver categories